Development of Edu Pilot: A Web-Based Interactive Physics Laboratory on Temperature and Heat for High School Physics Learning - Rosyidah Rohmah; Nyoman Sudana Degeng; Nurmida Nurmida; Catherine Sitompul (FKIP - Universitas Riau, 2026)
This study was initiated by pre research questionnaire results from high schools students in Indonesia, revealing difficulties in understanding temperature and heat topics. The data showed that students required visual media/interactive simulations to conceptualize conduction, convection, and radiation concretely, and demanded flexible web-based and virtual laboratory learning tools for independent study. This study aims to develop and test the feasibility, practicality, and effectiveness of a web based physics learning platform named Educational Physics Interactive Laboratory of Thermal Transfer (EDU PILOT). The research and development (R&D) method was applied involving eleventh-grade students of SMA Hang Tuah 2 Sidoarjo. The validation results showed feasibility percentages of 89.1% from media experts, 91.6% from product design experts, and 94% from material experts, all categorized as highly feasible. The small group trial achieved an average score of 84% (very good), while the field trial score reached 83% (very good). Usability testing verified that the system performs exceptionally well with an overall average score of 84% (very good) and also based on pre-test and post-test analyses. So, it can be concluded that the Educational Physics Interactive Laboratory of Thermal Transfer platform is highly feasible and practical for use as high school physics learning medium for temperature and heat.